Epileptiform activity in brain organoids derived from patient with Glucose Transporter 1 Deficiency Syndrome - Müller, Y.; Lengacher, L.; Friscourt, F.; Quairiaux, C.; Stoppini, L.; Magistretti, P. J.; Lengacher, S.; Finsterwald, C. (Frontiers in Neuroscience, 2024)
IntroductionGlucose Transporter 1-Deficiency Syndrome (GLUT1-DS) is a rare genetic disorder caused by mutations in the gene encoding for GLUT1 and characterized by impaired glucose uptake in the brain. This leads to brain hypometabolism and the development of symptoms that include epilepsy, motor dysfunctions and cognitive impairment. The development of patient-specific in vitro models is a valuable tool for understanding the pathophysiology of rare genetic disorders and testing new therapeutic interventions.MethodsIn this study, we generated brain organoids from induced pluripotent stem cells (iPSCs) derived either from a GLUT1-DS patient or a healthy individual. The functional organoids were analyzed for cellular composition, maturity, and electrophysiological activity using a custom-made microelectrode array (MEA) platform, which allowed for the detection of spikes, burst patterns, and epileptiform discharges.ResultsImmunostaining revealed a similar distribution of neurons and astrocytes in both healthy and GLUT1-DS brain organoids, though GLUT1-DS brain organoids exhibited reduced cellular density and smaller overall size. Electrophysiological recordings demonstrated functional spike profiles in both organoid types. Notably, our study demonstrates that brain organoids derived from a GLUT1-DS patient exhibit distinct epileptiform activity and heightened sensitivity to glucose deprivation, reflecting key features of the disorder.DiscussionThese findings validate the use of brain organoids as a model for studying GLUT1-DS and highlight their potential for testing novel therapeutic strategies aimed at improving glucose metabolism and managing epilepsy in patients.